Morphology Description, Subtyping, Distribution And Phylogeny Of Blastocystis Sp. In Livestock Animals Of Two West Coast States In Malaysia - Adedolapo Aminat, Rauff Adedotun (2023)
Blastocystis sp. is a unicellular, anaerobic protist inhabiting the intestinal tract of diverse animal hosts, including humans. It is a fascinating organism with various aspects of its biology, and epidemiology, even though the pathogenicity is still unknown. In Malaysia, the livestock industry is a continuously growing sector, providing a good source of protein, employment to the general population, and an avenue for constant human-animal contact. This study was aimed at investigating the morphological description, subtypes, distribution, and phylogeny of Blastocystis in livestock animals from Penang and Perak, Malaysia, and the possible role of livestock animals in the transmission of this organism to humans. A total of 701 livestock animals were examined for Blastocystis infection in Penang and Perak, Malaysia. In Penang, fresh faecal samples from 127 cattle, 149 goats, 100 sheep, and caecal contents from 174 quails were subjected to in-vitro cultivation using a modified Jones medium. Forms and dimensions of Blastocystis cells from these hosts were assessed using light microscopic observations of Giemsa-stained slides, while electron microscopy was used to describe the surface structure of selected isolates. DNA barcoding method was used for subtype identification; thereafter, phylogenetic analyses of sequences obtained were carried out.